Kajian Kelayakan Pembentukan Sentra Peternakan Sapi di Sumatera Utara (Studi Kasus Kabupaten Batubara) - Vanhuri, Eddi; Hasnudi, Hasnudi; Lubis, Yusniar (Universitas Medan Area, 2019)
The aims of study to analyze the feasibility of cow farming center in Batubara Regency from financial aspect and non financial aspect, and to analyze the pattern of development of cow farming center in Batubara Regency. This research using a quantitative approach with survey on the type of research. The sample was determined by simple random sampling method, 50 people. The data collection through questionnaires. Data were analyzed using financial feasibility and non financial feasibility. The results showed that the cow farming center in the Batubara Regency from the investment criteria of business activities is feasible, the R / C value is 1.61. The cow farming center in Batubara Regency based on nonfinancial aspects is feasible in terms of market, social, economic, and cultural aspects as well as environmental aspects. Meanwhile, from the technical aspects, management and legal aspects, still need to be addressed. The development of cow farming center in Batubara Regency can be done with the pattern of community livestock with the system of integration to the surrounding areas by arranging and cooperation between various related parties, especially the plantation, that is: the area integration of cow-palm; cow-rubber integration areas; and the integration of cow-food crops.